Identifikasi Potensi Pengembangan Lanskap Wisata Pertanian di Kawasan Kedung Kayang Kabupaten Magelang - Aini, Lis Noer (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
The research aims to identify the development potential of Kedung Kayang as agritourism area to increase society welfare Kedung Kayang and vinicity. The method of this research was survey method by using observation and questioner. The data were analyzed descriptively and spatially, with primary and secondary data. Primary data consisted of perception about Kedung Kayang, while secondary data consisted of Magelang map, geographical position, soil kind, topography, climate and society social condition of Kedung Kayang and vinicity. The result of this research showed that Kedung Kayang area has natural potential i.e: waterfall, Merapi view, river, topograph, camping ground, and agricultural potential. The result of identification showed that Kedung Kayang has potential to be an agrotourism area.